Climate and group B streptococci colonisation during pregnancy: present implications and future concerns - Dadvand, P; Basagana, X; Figueras, F; Sunyer, J; Nieuwenhuijsen, MJ (BJOG : an international journal of obstetrics and gynaecology, 2011)
Please cite this paper as: Dadvand P, Basagana X, Figueras F, Sunyer J, Nieuwenhuijsen M. Climate and group B streptococci colonisation during pregnancy:present implications and future concerns. BJOG 2011;118:1396–1400. The available evidence on the impact of climate on human bacterial infections is very limited. We studied the impact of climatic factors on maternal group B streptococci (GBS) colonisation during pregnancy in Barcelona, Spain, in the period 2001–2005. Averages of daily temperature, relative humidity, and heat index (perceived temperature) over weeks 32–36 of gestation, measured by the closest of three meteorological monitors to the maternal place of residence were assigned to each subject. Logistic regression models were developed to extract adjusted odds ratios for continuous and categorical (quartiles) exposures. We detected increased risks of GBS colonisation in higher ambient temperatures and humidity.